Neurophysiological studies of patients with classical phenylketonuria: evaluation of results of IQ scores, EEG and evoked potentials - Coşkun, Turgay; Topçu, Meral; Üstündağ, İncilay; Özalp, İmran; Renda, Yavuz; Ciğer, Abdurrahman; Nurlu, Gülay (The Turkish Journal of Pediatrics, 1993)
Neurophysiological studies were conducted in 42 patients with classical phenylketonuria. The results of the intelligence quotient scores, electroencephalogram, visual evoked potentials and brain-stem auditory evoked potentials were evaluated. When compared with the controls, the subjects demonstrated a significant prolongation in VEP P₁ and BAEP I-V interpeak latencies and an increase in VEP N₁P₁ amplitudes. No relationship was found between these pathological responses and metabolic control. However, the observation of normal intelligence quotient scores in 14 out of 18 patients who displayed a pathological prolongation in P₁ latencies led us to the conclusion that evoked potentials may have a significant role in the determination of neurophysiological defects and that even cases with good metabolic control may have some obscure neurophysiological dysfunction which should be evaluated more carefully.
Keywords: phenylketonuria; intelligence quotient; electroencephalogram; evoked potentials